2007
DOI: 10.1097/01.anes.0000271871.07395.ad
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of Procalcitonin to Diagnose Postoperative Infection after Cardiac Surgery

Abstract: Procalcitonin is a valuable marker of bacterial infections after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 38 publications
2
42
1
10
Order By: Relevance
“…OAR is a major abdominal operation, but unlike general surgery, it represents a -clean‖ intervention, as respiratory, alimentary, and genitourinary tracts are not involved, thus infections are expected to be lower in this field. According to most of the aforementioned studies, 10,11,15,[19][20][21] we focused our attention on the evaluation of only infectious complications. In our series, 29% of patients developed infectious complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OAR is a major abdominal operation, but unlike general surgery, it represents a -clean‖ intervention, as respiratory, alimentary, and genitourinary tracts are not involved, thus infections are expected to be lower in this field. According to most of the aforementioned studies, 10,11,15,[19][20][21] we focused our attention on the evaluation of only infectious complications. In our series, 29% of patients developed infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…During the first and second postoperative day (POD), PCT concentrations are more frequently elevated in patients after major surgery compared with patients undergoing minor operations. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Previous studies assessed PCT and its relationship with adverse postoperative events, mainly with regard to cardiac surgery, 8.22 whereas very little evidence exists so far regarding infectious complications after aortic surgery. [23][24][25][26] One of the most relevant aspects of PCT is its good specificity (SP), which has been recently demonstrated in the detection of postimplantation syndrome after endovascular repair.…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Procalcitonin (PCT) has already been tested in cardiac surgery to detect postoperative infection, but its role remains controversial. Some authors clearly describe a relation between PCT and the onset of postoperative infection [16] and also ventilator-associated pneumonia [17]. Other authors, such as Chakravarthy et al [18], found no significant difference in serum PCT levels between patients with and those without bacterial infection after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6 Another study conducted in Department of Anesthesiology and Critical Care, and Department of Pharmacy, Military Hospital, Tunis University, Tunis to compare the accuracy of PCT to diagnose postoperative infection after cardiac surgery and compare it with those of C-reactive protein, white blood cell count, and interleukins 6 and 8 concluded that PCT is a valuable marker of bacterial infections after cardiac surgery. 8 This study was conducted to evaluate the sensitivity of PCT compared to leucocyte count in the diagnosis of bacterial infection after surgery in patients who underwent major surgery at Dr. Sardjito General Hospital, Yogyakarta.…”
Section: Introductionmentioning
confidence: 99%
“…Serum PCT level showed a better predictor than leucocyte count to detect an infection caused by S. negative-coagulase growth. 22 Although many studies reported that serum PCT level had a high predictive value in detecting infection after surgery, [18][19][20][21][22] however, a study conducted in patients who underwent elective spinal urgery gave different result, as serum PCT level in general remained at <0.25 ng/mL during the postoperative course. Moreover, serum PCT level did not correlate with age, sex, DM, hypertension, BMI, operation time, operation site, or use of instrumentation.…”
mentioning
confidence: 99%